Spirits of the stone, from landlocked Laos to Sabah, insular Malaysia - Genovese, Lia (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2019)
This paper stems from data collected during fieldwork in the Laotian provinces of Xieng Khouang and Luang Prabang and in Malaysia’s Sabah province. It compares and contrasts the stone jars of Laos and the menhirs of Sabah, with particular focus on the supernatural qualities ascribed to stone. Jars and menhirs are expressions of a wider megalithic art, the former sculpted from a single boulder and the latter generally set vertically into the ground, plain and undecorated. Shape does not impact the stone’s perceived unearthly powers, whose spirit can manifest itself as easily from a jar as from a menhir. The relatively young age of the Sabah menhirs, estimated at 300 years, has been instrumental in assembling testimonies about their functions and ways in which communities interact with, and react to, their perceived paranormal qualities. The date of the Laotian jars is Iron Age.